(untitled) (SCIÉNDO INGENIUM, 2025)
In the emulsifier area of a food supply company, high temperatures and humidity generate thermal stress conditions that affect workers’ health and reduce their productivity. The lack of adequate environmental control exacerbates this situation, impacting operational efficiency. This research aims to evaluate the level of thermal stress at two levels in the emulsifiers area of a factory that manufactures chemical inputs for food, located in the district of Chorrillos, in the city of Lima, Peru. The WBGT index method is used, taking as a reference Standard RM No. 375-2008-TR, which also analyzes the metabolic consumption of workers. This study was conducted in the summer of 2024, using Criffer Protemp 4 and Inlite ITEMP thermal load monitors to determine environmental variables. The results obtained showed that the heat stress indices evaluated at workstations ET-01 and ET-02 were 34.9 and 35.6, exceeding the permitted limit values of 30.5 and 28.5, respectively. This situation represents a considerable risk to occupational health and creates a suboptimal work environment for the physical and mental performance of workers. In addition, operators showed a decrease in their work pace, as well as a higher frequency of unscheduled breaks and signs of fatigue at the end of the shift, affecting productivity in the area. Thermal load levels exceed the recommended thresholds for moderate work, indicating an urgent need to implement corrective measures, such as mechanical ventilation, controlled thermal breaks, or staff rotation. Overall, the results of thermal stress have a significant negative impact on the operational productivity of the area evaluated.